Avifaunal inventory of a Southern Amazonian transitional forest site: the São Luiz farm, Mato Grosso, Brazil - Mestre, Luiz Augusto Macedo; Rechetelo, Juliana; Cochrane, Mark Alan; Barlow, Jos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
This paper describes the avifauna sampled at the São Luiz farm, in Northern Mato Grosso State, a Southern Brazilian Amazonian forest site. The avifauna was sampled at forested and open sites, between 29 June and 27 July 2008, using point counts, mist-nets and general observations. We recorded 194 bird species within 18 orders and 46 families. The records of this study expanded the known range limits of at least 16 bird species. Despite the need for sampling in other seasons, the rarefaction curves indicate a representative sampling effort. The bird community observed at this site contains most of the species typically associated with Amazonian forests, south of the Amazon, and suggests that ‘transitional forests’ found at this site should be qualified as ‘Amazonian’ when considering their legal status. Our data highlights the importance of this anthropogenically-impacted and poorly-known region of Amazonia.
Keywords: Bird checklist; Amazonian Birds; Northern Mato Grosso; Southern Amazon